Working of heart beat touch sensor - S. , Rohith; R. , Puviarasi (International Journal of Psychosocial Rehabilitation, 2020)
Patient care is done in the presence of a doctor. But he can’t be there for everyone at once to provide medications and treatment for people. Therefore, constant observance of a patient is the correct one. However, the facility or accessibility for people in that particular geographic area. Therefore, this impressed North American nation decided to use different kinds of modules for the system that we have going to do. That method which is employed, used, for the people to check or verify their parameters, like heartbeat count. And we can intimate to the doctor whether there is any problem and send the known knowledge to the doctor. An IR-based heartbeat sensor can be contained in the system. This project or system can be able to counter find the heart rate by that system. The price of the device can be decided by what type of components or devices we have used in this project.